2007
DOI: 10.1002/cphc.200700465
|View full text |Cite
|
Sign up to set email alerts
|

Thin‐Film Infrared Spectroscopy of Acetonitrile

Abstract: Acetonitrile and [D3]acetonitrile in the vicinal region of a planar AgX fiber contain linear dipole-dipole linked oligomers as shown by 1) comparison of infrared band intensity ratios in the gaseous and condensed phases and 2) remarkable plots of absorbance (C--N stretch) versus time during evaporation from an AgX planar fiber element. The plots (CH3CN 2252 cm(-1), CD3CN 2262 cm(-1)) reveal the presence of octamers, hexamers, tetramers, and dimers along with some heptamer, trimer, and monomer structures. A nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 34 publications
1
42
0
Order By: Relevance
“…These additional facts may be important in understanding the mechanisms of the conversions. Although a fortunate choice of the experimental conditions may be important for the observed behavior, we have also observed steps (as in the evolution of the helices) in the evaporation of acetonitrile [5] and other solvents like dichloromethane (unpublished results) in the regular measurement of spectra on AgX.…”
Section: Discoveriesmentioning
confidence: 82%
See 2 more Smart Citations
“…These additional facts may be important in understanding the mechanisms of the conversions. Although a fortunate choice of the experimental conditions may be important for the observed behavior, we have also observed steps (as in the evolution of the helices) in the evaporation of acetonitrile [5] and other solvents like dichloromethane (unpublished results) in the regular measurement of spectra on AgX.…”
Section: Discoveriesmentioning
confidence: 82%
“…[6] TFIS has been used to make a spectroscopic identification of the oligomers of water [cyclic trimer, cyclic pentamer, cyclic hexamers (boat and chair), and bicyclic hexamers]. [7,8] TFIS utilizes a short acquisition time (revealing transient structures), limited IR energy (low signal, Sg, avoiding disruption of transient species), [5,6] and multiple reflections on planar AgX as the substrate for Fourier transform IR spectroscopy-attenuated total internal reflectance (FTIR-ATR), with limited penetration depth and molecular motion restricted by electrostatic immobilization. [8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] We acquired a series of NMT spectra at Sg 1000, and plotted the absorbances at a number of wavelengths versus time, as shown in Figure 1. For the first time, in many plots of this type, there were sharp changes in the absorbances at two of the wavelengths, an increase at 1637 cm À1 (p-helix) and a decrease at 1653 cm À1 (first p -helix) with a ratio (increase/decrease) of 2.2:1.…”
Section: Resultsmentioning
confidence: 99%
“…[1] An important result was that some of the infrared (IR) spectroscopic properties of a p-helix were found. The substantial increase in the p-helix content with increased substitution in the acyl portion suggested that an amide with a larger acyl group should be examined.…”
Section: Introductionmentioning
confidence: 98%